Uzbekistan searchung for military-political strategies in terms of geopolitical challenges - Bogdan Levyk (Cхід, 2013)
Military and political efforts of Uzbekistan in search of internal and external development strategy of the Republic after disintegration the Soviet Union and the proclamation of in dependence were analyzed. The authors how is the latest information about territorial and demographic characteristics. Current Constitution of security and defense was analyzed. The author considered the rights and responsibilities of the President I. Karimov on the issues and the work of the highest legislative body - Oliy Majlis. Structure, organization and legal basis of the national armed forces formation, their present staff and military-technical equipment, directions of transformation and modernization were described. The author characterized the basic functions of force structures, military organization of the state (the army, national security, counter-terrorism special forces, National Guard, Border Guard). The basic problems in the construction of the armed forces were determined. There is a detailed description of modern ensuring by weapons of military and air forces. Main relations hipswerede termined between the USA, Russian Federation and NATO in military-political sphere. The author listed specific international moves of Uzbekistan in combating against manifestations of terrorism and its contribution to the mission on Afghanistan's territory. The author analyzed the Military Doctrine of 2000, and its claims to neutralize the existing regional threats. Government action saga instmanife stations of religious extremism and terrorism were described. The author considered the question of international issues with neighboringcountries: Tajikistan and Kyrgyzstan on the use of Pamir water, pastures, electricity, gas. The role of inter governmental structures of the post-Soviet Collective Security Treaty, the Shanghai Cooperation Organization and GUUAM was determined. The author made area soned conclusion about the construction of Uzbekistan as multinational Islamic state with declarative elements of democracy.